Transformation of Livelihood Institutions and the Organization of Punan Dayak Communities in Berau District, East Kalimantan - Mardiyaningsih, Dyah Ita; Hadi Dharmawan, Arya; M Kolopaking, Lala; Firdaus, Muhammad; Reinhardt Nielsen, Martin (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
The social-ecological system of forests are changing with increasing modernity and has prompted the forest-dependent Dayak Punan community to adapt to the new conditions. In addition to changing livelihood structures, the institutional setting and social norms of subsistence strategies are also undergoing adaptation process. Therefore, the main question of this research is what institutional transformation are occuring of livelihoods in the Punan Dayak community as an adaptation to the modernity that entering the region where they live? A qualitative approach supported by quantitative data is used to obtain data and information in four Punan Dayak communities in Berau District, East Kalimantan. The level of dependence of Punan Dayak households on forests is declining, marked by increasing dominance of non-forest livelihood sources (i.e. wages and business). Institutions guiding the interaction between communities and the forest as a source of livelihoods, has also changed. In the four communities studied, the process of institutional transformation has produced four types of institutional organisations of subsistence vs. income dependent livelihoods, namely: subsistence-collective (livelihood activities to meet household food carried out in groups), subsistence-collective to commercial-contractual transition, commercial-collective (a livelihood activity aimed at earning money coordinated by the institution at the community level), and commercial-contractual (livelihood activities aimed at earning money/profits through formal working relationships individually or in groups).